(untitled) - Davis, Dick (Hoboken, N.J., 2008)
A pioneer in the financial media, Dick Davis has interacted with the investing public for over forty years. With his new book, he continues this trend. The first part of The Dick Davis Dividend contains an easy-to-read, yet profound discussion of the essentials of investing—focusing on the savvy veteran’s often unconventional, core beliefs. While the second part of this engaging guide makes a compelling case for combining both passive investing via index funds and active investing via stocks and mutual funds.
Keywords: Investments,Stocks,Portfolio management,Investment analysis